2021
DOI: 10.4103/jpbs.jpbs_146_21
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Impact of the COVID-19 Pandemic on Orthodontic Practice in the Middle East

Abstract: Background: With COVID-19 announced as a global pandemic, a countrywide lockdown was executed in many countries, including the Middle East. With no foregoing warning or expectation, orthodontic treatments were temporarily canceled as dental clinics and colleges were indefinitely closed. To the best of our knowledge, no study addresses the orthodontist perspective in such testing times, where they are entirely restricted to the confines of their homes. The study aims to assess the impact of the COVI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…A recent survey by the American Association of Orthodontists showed similar results, but they reported that 93% of orthodontists managing financial aspects received government/public funded support during the COVID-19 pandemic ( 11 ). Across the globe, revenue generation from orthodontic clinics fell during the COVID-19 pandemic due to a reduction in patient throughput, despite providers increasing their hours to provide improved treatment capacity and to try and compensate for the impacts of the pandemic to a limited extent ( 4 , 12 , 13 ). Cross infection measures, social distancing, Cancellations due to testing positive and the need for self-isolation, increased fail-to-attend rates, fallow times, and the time taken for increased cross-infection measures between patients all had a negative effect on productivity within the clinical environment.…”
Section: Discussionmentioning
confidence: 99%
“…A recent survey by the American Association of Orthodontists showed similar results, but they reported that 93% of orthodontists managing financial aspects received government/public funded support during the COVID-19 pandemic ( 11 ). Across the globe, revenue generation from orthodontic clinics fell during the COVID-19 pandemic due to a reduction in patient throughput, despite providers increasing their hours to provide improved treatment capacity and to try and compensate for the impacts of the pandemic to a limited extent ( 4 , 12 , 13 ). Cross infection measures, social distancing, Cancellations due to testing positive and the need for self-isolation, increased fail-to-attend rates, fallow times, and the time taken for increased cross-infection measures between patients all had a negative effect on productivity within the clinical environment.…”
Section: Discussionmentioning
confidence: 99%